1998
DOI: 10.1108/09556229810205240
|View full text |Cite
|
Sign up to set email alerts
|

Handling the assembly line balancing problem in the clothing industry using a genetic algorithm

Abstract: Assembly line balancing problems that occur in real world situations are dynamic and are fraught with various sources of uncertainties such as the performance of workers and the breakdown of machinery. This is especially true in the clothing industry. The problem cannot normally be solved deterministically using existing techniques. Recent advances in computing technology, especially in the area of computational intelligence, however, can be used to alleviate this problem. For example, some techniques in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 10 publications
0
31
0
2
Order By: Relevance
“…Tomastik, Luh, and Liu (1996) developed a low-order integer programming model using the Lagrangian relaxation method which integrated scheduling and resource allocation for a flexible manufacturing system. Chan, Hui, Yeung, and Ng (1997) used a GA to solve an assembly line balancing problem in the apparel industry and concluded that the GA was an appropriate tool to solve the dynamic and complex production scheduling problem. Wong, Mok, and Leung (2005) also developed a GA to balance an apparel assembly line of UPS and investigated the impact of different level of skill inventory on the assembly makespan.…”
Section: Nomenclaturementioning
confidence: 99%
“…Tomastik, Luh, and Liu (1996) developed a low-order integer programming model using the Lagrangian relaxation method which integrated scheduling and resource allocation for a flexible manufacturing system. Chan, Hui, Yeung, and Ng (1997) used a GA to solve an assembly line balancing problem in the apparel industry and concluded that the GA was an appropriate tool to solve the dynamic and complex production scheduling problem. Wong, Mok, and Leung (2005) also developed a GA to balance an apparel assembly line of UPS and investigated the impact of different level of skill inventory on the assembly makespan.…”
Section: Nomenclaturementioning
confidence: 99%
“…Các chi tiết được quy về hình chữ nhật để sắp xếp trước khi cắt, với chiều dài cuộn vải được giả định là không giới hạn. Trong vấn đề thiết kế chuyền may có đề tài của nhóm tác giả Chan và cs, Chen và cs đã sử dụng thuật toán di truyền GA để thiết lập cân bằng chuyền 13,14 . Đề tài của Chang và cs đã sử dụng thuật toán GA để phát triển một hệ thống hỗ trợ quyết định cho sản xuất hàng may mặc 15 .…”
Section: Giới Thiệuunclassified
“…For example, Chan et al (1998) developed a GA to solve SMALB Type-1 problem in the clothing industry in order to maximise line efficiency. For example, Chan et al (1998) developed a GA to solve SMALB Type-1 problem in the clothing industry in order to maximise line efficiency.…”
Section: Literature Overview Of Ga In Albpmentioning
confidence: 99%